Urine Metabolomics Study on Potential Hepatoxic Biomarkers Identification in Rats Induced by Aurantio-Obtusin - Longlong Xu; Longlong Xu; Yuguang Wang; Zengchun Ma; Xianglin Tang; Yue Gao; Yue Gao (Frontiers Media S.A., 2020)
Previous studies revealed the hepatotoxic effect of aurantio-obtusin on rats. The aim of this study was to identify potential biomarkers of urine caused by aurantio-obtusin. Sprague-Dawley (SD) rats with body weight of 0, 4, 40, and 200 mg/kg were orally given aurantio-obtusin for 28 days, and urine was collected for 24 h after the last administration. The urine metabolites in the aurantio-obtusin group and the control group were analyzed by ultraperformance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-QTOF/MS). Twenty-three metabolites were identified as potential biomarkers, and 10 of them were up-regulated, including xanthosine, hippuric acid, 5-L-glutamyl-taurine, etc. The other 13 biomarkers were down-regulated, including thymidine, 3-methyldioxyindole, cholic acid, etc. The significant changes of these biomarkers indicated that purine metabolism, taurine and hypotaurine metabolism, primary bile acid biosynthesis, pyrimidine metabolism, and tryptophan metabolism played an important role in the hepatotoxicity of aurantio-obtusin in rats. In this paper, the safety and potential risk of aurantio-obtusin were studied for the first time by combining the toxicity of aurantio-obtusin with the results of urine metabolomics, which provided information for the mechanism of liver injury induced by aurantio-obtusin.